2010
DOI: 10.1007/s12562-010-0214-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity and temperature on salinity tolerance of the sea cucumber Apostichopus japonicus

Abstract: Sea cucumber Apostichopus japonicus juveniles acclimated to different environmental conditions (23, 25, and 27°C combined with 25, 30, and 35 psu) were assessed for tolerance to increasing and decreasing levels of salinity at a rate of 2 psu h -1 . They were also tested for the LS 50 (median lethal salinity) when transferred directly into a series of higher salinity (32-46 psu) and lower salinity (9-25 psu). The CSMax (critical salinity maximum), CSMin (critical salinity minimum), USTL (upper salinity tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 9 publications
0
19
0
2
Order By: Relevance
“…In the shrimp, Litopenaeus vannamei, thermal tolerance was increased by the combined effects of acclimation temperature and salinity (Kumlu et al, 2010), though acclimation temperature had a stronger influence than salinity on thermal tolerance. In contrast, in the sea cucumber, Apostichopus japonicus, salinity tolerance limits were positively affected by acclimation to increased salinity, but negatively affected by acclimation to increased temperature (Hu et al, 2010). The simultaneous effects of temperature and salinity acclimation have not been demonstrated for Daphnia, though salinity has been shown to alter Daphnia tolerance limits to other stressors, such as heavy metals (Bossuyt et al, 2005).…”
mentioning
confidence: 96%
“…In the shrimp, Litopenaeus vannamei, thermal tolerance was increased by the combined effects of acclimation temperature and salinity (Kumlu et al, 2010), though acclimation temperature had a stronger influence than salinity on thermal tolerance. In contrast, in the sea cucumber, Apostichopus japonicus, salinity tolerance limits were positively affected by acclimation to increased salinity, but negatively affected by acclimation to increased temperature (Hu et al, 2010). The simultaneous effects of temperature and salinity acclimation have not been demonstrated for Daphnia, though salinity has been shown to alter Daphnia tolerance limits to other stressors, such as heavy metals (Bossuyt et al, 2005).…”
mentioning
confidence: 96%
“…Several authors have reported that temperature had significant effects on survival rate and also associated with salinity. 100% survival rate was reported at 23, 27, 25°C for normal salinity of sea water for A. japonicus (Hu et al, 2010). Chu Yuan kee et al (2007) found that, B. marmorata displayed 100% survival rate at salinity 25 and 35 ppt and 91,67% and 66,65% survival rates in temperature 28 and 32°C, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researches on sea cucumber rearing especially in the Far East and Asian countries has been considered more and more. There are plenty of studies focused on physicochemical parameters effects on growth of tropical sea cucumbers (Hamel and Mercier, 1996;Kashenko, 2002;Asha ve Muthiah, 2005;Wang et al, 2008;Hu et al, 2010). One of the most physicochemical parameter that effecting growth of sea cucumberis the temperature (Dong et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…C-type lectins from other molluscs might follow different evolutionary pathways and play different functions in vivo [30]. In sea cucumber, the innate immune system is particularly important, because echinoderms lack the immune system that is later evolved in vertebrates [24]. The ability to recognize the exposed glycans on the cell surface of potential pathogens by host humoral or cell-associated lectins is considered as a key function of innate immunity and a primary role of PRRs [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there were a number of studies on A. japonicus done in recent years. This sea cucumber is epibenthic and occurs along the coastlines of temperate Asia [24]. It belongs to the Echinodermata, Eleutherozoa, Holothuroidea, Aspidochirota, Stichopodidae, Apostichopus, A. japonicus [25].…”
Section: Introductionmentioning
confidence: 99%